2022
DOI: 10.1177/00027642221075261
|View full text |Cite
|
Sign up to set email alerts
|

Digital Anticipation: Facilitating the Pre-Emptive Futures of Chinese Grandparent Migrants in Australia

Abstract: In this article, we contrast the digital kinning and digital homing practices of PRC Chinese transnational grandparents in Australia from two migration cohorts. Our case studies demonstrate that these digital practices form an integral part of the ability to anticipate aging futures. This “digital anticipation” not only helps to safeguard and affirm social and cultural identities that are often at risk as people age in migrant settings, but also provides the potential to imagine either a future return to China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Our data clearly indicate that access to digital kinning and digital homing practices can significantly improve the social support and cultural and social identities and dignity of older adults in residential care (Baldassar et al., 2021). Currently, there is no policy governing digital access in care homes, and provision is patchy, with many homes existing in ‘black spots’ (Baldassar et al., 2022).…”
Section: Visits Over Timementioning
confidence: 62%
See 1 more Smart Citation
“…Our data clearly indicate that access to digital kinning and digital homing practices can significantly improve the social support and cultural and social identities and dignity of older adults in residential care (Baldassar et al., 2021). Currently, there is no policy governing digital access in care homes, and provision is patchy, with many homes existing in ‘black spots’ (Baldassar et al., 2022).…”
Section: Visits Over Timementioning
confidence: 62%
“…Our data clearly indicate that access to digital kinning and digital homing practices can significantly improve the social support and cultural and social identities and dignity of older adults in residential care (Baldassar et al, 2021).…”
Section: Ageing and Migration Study And Visits Todaymentioning
confidence: 69%
“…Regarding the digital gap, findings were mixed for older migrants’ attitudes towards digital adaptation in studies of different host and home regions. For example, Baldassar et al’s (2022) study on Chinese grandparent migrants in Australia found that older migrants become more motivated and active in learning to use digital technologies after migration. However, Goodall et al’s (2010) study on Italian/Greek older migrants in Australia (i.e.…”
Section: Cross-border Ageing By Older Migrants In the Digital Agementioning
confidence: 99%
“…Existing literature demonstrates the context-specific responses of older migrants to the digital gap, their patterns of use in the host region, as well as how digital use impacts their integration and everyday lives in the host region. Previous research found that mobile app adoption in host region is dependent on older migrants’ socio-demographics, reasons for migration, and host- and home-region characteristics such as digitalization level (Baldassar et al, 2022; Goodall et al, 2010; Hunter, 2015; Nguyen et al, 2022). In the context of the GBA, existing research on cross-border ageing engaged by Hong Kong older adults in the GBA has mainly focused on cross-border portability of welfare (Cao, 2020), while social inclusion and the way their everyday lives are influenced by the digital gaps in terms of mobile app adoption lack comprehensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Grandparents play an important role in instructing their grandchildren in religious, cultural, and family values, promoting bilingualism, and introducing them to extended family. Co‐residing grandparents often undertake substantial caring and domestic responsibilities (Baldassar et al., 2022; Ho & Chiu, 2020; Schuler et al., 2022); however, they are sometimes susceptible to depression, loneliness, and mental distress (Ferrer et al., 2020; Guruge et al., 2019). There is limited academic and policy attention paid to transnational globalized and flexible families despite their increasing prevalence in Canada (Mujahid et al., 2011) and the strong presence of family reunification in Canada's immigration framework (Gaucher, 2018).…”
Section: Introductionmentioning
confidence: 99%